Evaluation of Nozzle Temperature and Infill Speed on the Mechanical Strength of 80:20 PP/UHMWPE Blends via Fused Filament Fabrication (FFF) for Biomedical Applications - Siti Nur Hanifah Zamri; Khairu Kamarudin; Mohd Khairuddin M.S; Shahrul Izwani Christopher; Fakhrul Nur Aiman; Shufeng Sun (Progress in Engineering Application and Technology, 2026)
This study focused on the development and optimization of 3D-printed Polypropylene (PP)/Ultra-High Molecular Weight Polyethylene (UHMWPE) at an 80:20 ratio to address the mechanical limitations of PP and the thermal constraints of UHMWPE. The effects of nozzle temperature (250 ̊C and 260 ̊C) and infill speed (29 mm/s and 32 mm/s) on mechanical performance were systematically investigated. Tensile and impact tests were conducted, and interlayer adhesion was evaluated using Scanning Electron Microscopy (SEM). Printing parameters were optimized using the Taguchi design of experiments (DOE) method in Minitab, with emphasis on maximizing impact strength. The results showed that higher nozzle temperatures combined with appropriate infill speed significantly improved tensile strength, impact resistance, and interlayer bonding. These findings demonstrate that optimized 3D printing parameters can effectively enhance the structural performance of PP/UHMWPE composites, supporting their potential use in lightweight, durable, and high performance applications, including biomedical components.